Systematics and morphology of American mosasaurs - Russell, Dale A. (Peabody Museum of Natural History, Yale University, 2020)
"Presents the complete, classic 1967 monographic revision of the mosasaurs then known from North America, which was the foundation the modern era of mosasaur research, describing mosasaur form and function, their habits and habitats, and their phylogenetic relationships from the species level to more inclusive taxa"--